Open repair of a ruptured abdominal aorta with an aortoiliac vein fistula in a 7-month-old infant and review of the literature - Olivia I. Fuson, BA; Kelsi Hirai, MD; Devin R. Halleran, MD; Mubeen Jafri, MD, FACS, FAAP; Ashok Muralidaran, MD, FACS; Amir Azarbal, MD, MCR; Cherrie Z. Abraham, MD, FRCSC; Sherene Shalhub, MD, MPH, FACS, DFSVS (Journal of Vascular Surgery Cases and Innovative Techniques, 2024)
Ruptured abdominal aortic aneurysms are extremely rare in the pediatric population. In this video case report, we describe the successful repair of a ruptured abdominal aortic aneurysm in a 7-month-old female infant.